2021
DOI: 10.15294/jubk.v10i2.47991
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Student Engagement: The Mediation Effect of Self Esteem

Abstract: Student engagement in learning is essential in creating active, creative, and fun learning. Unfortunately, not all students are engaged cognitively, emotionally, and behaviorally in learning. This study intends to prove that self-esteem can mediate the relationship between mindfulness and student engagement. This correlational study involved 469 students from four Senior/Vocational High schools in East Lampung Regency. The result of this study revealed that mindfulness predicts higher self-esteem. Mindfulness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…Low level of mindfulness allows the brain to search and concentrate on the stressing factors, resulting in the intensification of the negative affective response and therefore impeding resilience. The findings of the study are congruent with the one carried out by Artika et al ( 2021 ) who demonstrated mindfulness predicts learners' engagement and mindfulness is highly critical to contribute to renewing learners' cognition and affection and reinforce their engagement while learning. It is represented in tasks involving fun learning which possibly allows learners have a higher sense of comfort, lower fear, and pleasance during studying.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Low level of mindfulness allows the brain to search and concentrate on the stressing factors, resulting in the intensification of the negative affective response and therefore impeding resilience. The findings of the study are congruent with the one carried out by Artika et al ( 2021 ) who demonstrated mindfulness predicts learners' engagement and mindfulness is highly critical to contribute to renewing learners' cognition and affection and reinforce their engagement while learning. It is represented in tasks involving fun learning which possibly allows learners have a higher sense of comfort, lower fear, and pleasance during studying.…”
Section: Discussionsupporting
confidence: 88%
“…The degree of interest, concentration, optimism, passion, inquisitiveness, or incentive learners experience while learning or teaching is called engagement (Derakhshan et al, 2022 ); and it is characterized as multidimensional, regularly evaluated based on what learners do, think, and feel that have a straightforward relation with education (Fredricks et al, 2019 ). Learners' engagement is significant in educational activities because learners should dynamically take part in the educational cycle (Artika et al, 2021 ) and it can be witnessed through learners' focus, attractiveness, and ease in attaining education (Widyaswara et al, 2019 ), and it is taken into consideration as a pretty suitable and crucial precondition of learning in EFL classrooms (Dörnyei, 2019 ). Engaging in education is lively and self-motivated and is likely to have favorable outcomes in the educational presentation (Reschly and Christenson, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Students who can evaluate themselves positively will develop high self-esteem and be more involved in activities on campus. This finding is in line with the research results of Artika et al (2021). They found that self-esteem can predict student engagement.…”
Section: Discussionsupporting
confidence: 92%
“…Pellas (2014) found that among students, self-esteem is a predictor of the three dimensions of student engagement. Artika, Sunawan, and Awalya (2021) also found that self-esteem has a significant effect on student engagement. According to Rosenberg et al (1995), self-esteem is an individual's positive or negative attitude toward himself and the individual's overall evaluation of his thoughts and feelings.…”
Section: Introductionmentioning
confidence: 79%